Pengaruh Pemberian Silase Rumput Kume dan Alysicarpus vaginalis dengan Imbangan yang Berbeda Terhadap Total Digestible Nutrien (TDN) dan Retensi Nitrogen pada Sapi Persilangan Ongole Brahman - Maria Serlin; Gustaf Oematan; Imanuel Benu (Animal Agricultura, 2023)
This study aims to determine the administration of kume grass silage and Alysicarpus vaginalis with different balances on total digestible nutrient (TDN) and nitrogen retention in ongole brahman crossbreed cattle. In this study, 4 ongole Brahman cross cattle were used with an age range of 8-12 months, and a body weight range of 137.0 -200 kg, with an average body weight of 167.25 kg. The research method used was the Latin square design method (RBSL) with 4 treatments and 4 replications. The treatment used in this study was silage feed consisting of: P0: Kume grass 64% + 36% concentrate feed, P20: Kume grass 51.2% + Alysicarpus vaginalis 12.8% + 36% concentrate feed, P40: Kume grass 38.4% + Alysicarpus vaginalis 25.6% + 36% concentrate feed, P60: Kume grass 25.6% + Alysicarpus vaginalis 38.4% + 36% concentrate feed. The variables measured were TDN, N consumption, urine N production, faecal N production, and N retention. Data were analyzed using Analysis of Variance (ANOVA), and if there was a difference then it was continued with Duncan's further test. The results showed that the administration of kume grass silage and Alysicarpus vaginalis with different balances up to a level of 60% had no significant effect (P>0.05) on the TDN value, stool N production, urine N production, but had a very significant effect (P<0,01) on the N retention value. It was concluded that the administration of kume grass silage and Alysicarpus vaginalis with different proportions up to a level of 60% decreased TDN values, N retention, N consumption, fecal N production and urine N production.